The trap of the aesthetics of existence, or the foucauldian left in the neoliberal labyrinth - Leomir Hilario (Argumentos)
The “last Foucault” investigated the “practices of the self” that marked ancient philosophy not only with a historical objective, but also to offer his contemporaries an ethical-political horizon marked by a way of life called “aesthetics of existence”. However, how does the emergence of neoliberalism impact this horizon? Mapping two distinct traditions, the Foucauldian left and right, as well as proposing the existence of a “double Foucault” – exoteric and esoteric – I defend a reading that goes beyond Foucault, positioning Deleuze as an important inflection point.